Design, simulation, and testing of a magnetorheological fluid–based haptic actuator for mobile applications. (September 2015) - Ryu, Semin; Koo, Jeong-Hoi; Yang, Tae-Heon; Pyo, Dongbum; Kyung, Ki-Uk; Kwon, Dong-Soo
This article presents a novel design of a miniature haptic actuator based on magnetorheological fluids for mobile applications with the aim of providing various haptic sensations to users in mobile devices. The primary design goal for a haptic actuator for mobile applications is to miniaturize its size while achieving large forces and low power consumption. To this end, this study proposes to design the actuator's piston head (or plunger) in cone shape and activate multiple modes of magnetorheological fluids. A prototype actuator was designed and fabricated based on a simulation model. Using a dynamic test frame, the performance of the prototype actuator was evaluated in terms of the force (resistive force) produced by the prototype. The results show that the small actuator (10 mm × 10 mm × 6.5 mm) produced a maximum resistive force of about 5 N and the force rate of nearly 80% at 0.3 W. This change in resistive force or the force rate is sufficient to provide several steps of force variation that is explicitly perceivable for operators, depending on the input power. The results demonstrate a feasibility of using the proposed actuator's applications in mobile devices, conveying realistic haptic sensations to users.